18.4L: Late‐News Paper: Full Color Flexible Top‐emission AMOLED Display on Polyethylene Naphthalate (PEN) Foil with Metal Oxide TFTs Backplane. Issue 1 (1st July 2013) - Fukui, Yusuke; Shibata, Masaomi; Tanaka, Yuji; Okumoto, Kenji; Morita, Kiyoyuki; Otake, Keiichi; Tripathi, Ashutosh Kumar; van der Putten, Bas; van der Steen, Jan‐Laurens; Tempelaars, Karin; van Leuken, Linda; Li, Flora; et al.
Abstract We have developed a full color flexible top‐emission AMOLED display with 80 ppi resolution using In‐Ga‐Zn‐O TFT backplane on PEN foil under the maximum process temperature of 150 oC. Notwithstanding the low processing temperature, the TFTs with SiOx passivation layer show high reliability with VTH shift of less than 0.2 V at 10, 000 seconds under bias‐stress of −10 V.